PERLINDUNGAN HUKUM BAGI PIHAK-PIHAK YANG BERITIKAD BAIK DALAM PEMBATALAN PERJANJIAN JUAL BELI TANAH DAN BANGUNAN (Studi Kasus Nomor 29/Pdt. G/2014/PN. Wsb) - KERI SANTOSA; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The purpose and this study is to know the Legal Protection for Good-Strong Parties in Cancellation of Sale and Purchase Agreement of Land and Banguan (Study of PN Decision No. 29 / Pdt.6 / 2014 / PN.wsb). This research is empirical law research, that is research based on implementation in effort to get primary data preceded by library research to obtain secondary data. The research was conducted at Notary Office / PPAT, and all data obtained were analyzed quantitatively. Based on the analysis, the authors conclude several things Legal protection against the good-willed (buyer) in the sale and purchase agreement of land and building if the seller cancel the agreement, then for the signature of partial signing by the parties is a must.Judge's Consideration on Legal Protection for Good-Predicted Parties In Cancellation JuaL Purchases Land and Buildings where the Public Prosecutor should be thorough and careful in preparing the indictment, since the indictment is the basis for the judge to impose or not to bring down the defendant faced beforehand the court, in addition, must also have knowledge or knowledge of the law well, not only the law in formal, but also the law materially so as not wrong in determining where the deeds in accordance with the elements that are indicted. As for constraints and solutions Legal Protection Both parties who are intent on canceling Land and Building Sell To know whether the buyer has good intentions or not, then there must be a way of measuring it, that is by finding out the activeness of the buyer, where the buyer is obliged to examine the material facts and the juridical facts of the object of the transaction. If the buyer has been actively researching related to the material facts of the object of the transaction, then he can be considered as a good-faith buyer who gets legal protection, To know whether the buyer is well or not, then there must be a way of measuring it, that is by finding out the liveliness of the buyer where the buyer is obliged to examine the material facts and juridical facts of the object of the transaction. If the buyer has actively examined the material facts related to the object of the transaction, then he may be considered a good-faith buyer who has legal protection Keywords: Legal Protection, Cancellation of Sale and Purchase of Land and Building